2014
DOI: 10.1111/ceo.12376
|View full text |Cite
|
Sign up to set email alerts
|

HIF1A as a major vascular endothelial growth factor regulator: do its polymorphisms have an association with age‐related macular degeneration?

Abstract: No associations appeared between HIF1A SNPs and AMD, which were studied here for the first time; however, polymorphism rs1061170 of the CFH gene is associated with AMD in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Interestingly, Okur et al . did confirm a statistically significant association of a specific SNP of the CFH gene, rs1061170, and AMD in the studied population …”
supporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, Okur et al . did confirm a statistically significant association of a specific SNP of the CFH gene, rs1061170, and AMD in the studied population …”
supporting
confidence: 58%
“…In this issue, Okur et al . report on the investigation into the association of polymorphisms of HIF1A (encoding the HIF‐1α protein), and other related genes, with AMD …”
mentioning
confidence: 99%
“…Furthermore, resveratrol regulates gene expression to exert its biological function, while the understanding of its regulatory mechanism is not sufficiently known. Importantly, resveratrol has been reported to be a potential epigenetic factor [24], and the current investigations indicated the regulatory role of resveratrol in DNA methylation [25] and histone modification [26], suggesting that resveratrol also probably exerts its hepatic protection function through regulating the modification of m 6 A.…”
Section: Introductionmentioning
confidence: 65%
“…Also, Lin et al [ 33 ] reported that the HIF1A 1790 G/A might be played a protecting role significantly to develop the lumbar disc degeneration (LDD), and HIF1A 1772 C/T did not play any role with the severity of LDD. Some authors also checked the association of the HIF1A gene with cellulite [ 28 ], hemodialysis patients [ 30 ], high-altitude polycythemia (HAPC) [ 36 ], and age-related macular degeneration (AMD) [ 23 ]. They found the significant association of HIF1A with cellulite, and insignificant association of HIF1A with hemodialysis patients, HAPC and AMD risk.…”
Section: Introductionmentioning
confidence: 99%